A study of the ichnology, lithology and reservoir quality of the Palaeogene Grumantbyen Formation on Svalbard - Øygard, Ørjan Berge (The University of Bergen, 2016)
The Palaeogene Grumantbyen Formation is one of the least understood formations in the geology of Svalbard. The objective of this thesis was to get a better understanding of the sedimentological development and depositional environment of the formation through detailed ichnological, lithological and petrographical studies. Finally, a detailed description of the reservoir quality of the formation will be presented. The Grumantbyen Formation is highly bioturbated throughout the whole succession with only few signs of physical sedimentary structures. The ichnological study has led to an interpretation of seven different ichnofabrics occurring in the formation. There is a gradual transition between these ichnofabrics, and they are implying a change from a distal to a more proximal environment from the bottom to the top of the succession. 5 different lithofacies have been interpreted, and they show that the succession is gradually coarsening and shallowing upward from an offshore deposited sandy siltstone towards an upper shoreface deposited light silty sandstone. A gravel layer appearing erosional on top of the upper shoreface deposited lithofacies has been interpreted to represent a transgressive lag associated with the major flooding of the Grumantbyen Formation, and deposition of the superimposed Frysjaodden Formation. The petrographical study shows a gradual increase in grain-size, better sorting, roundness, shape of the grains and decrease in matrix from the most distal towards the most proximal-lithofacies. This suggests that the energy conditions are getting stronger as a result of a gradual shallowing upward trend in the succession. The formation's appearance of glauconite in combination with high bioturbation intensity, lack of physical sedimentary structures and sandy input, has in this study been interpreted to represent a system with very little sediment input. A possible low, but continuous sediment input, which was greater than the available accommodation space is suggested, in order to have suitable ...